Cadmium Toxicity Affects Phytochemicals and Nutrient Elements Composition of Lettuce (Lactuca sativa L.) - Sani Ahmad Jibril; Siti Aishah Hassan; Che Fauziah Ishak; Puteri Edaroyati Megat Wahab (Advances in Agriculture)
Lettuce varieties Bombilasta BBL and Italian 167 were treated with different concentrations of cadmium (0, 3, 6, 9, and 12 mg/L) in a nutrient film technique (NFT) system to study its toxicity on phytochemicals and nutrient elements. Antioxidants analysis which employed DPPH and FRAP, flavonoids, phenolic, vitamin C, malondialdehyde (MDA), and proline indicated significant effects of Cd treatment on the varieties tested. Different concentration levels of Cd lead to positive interactions in FRAP, phenolic, and MDA but no significant effect in flavonoids, vitamin C, and proline. Contents of macro- and microelements in the varieties were significantly affected with increase in the toxicity levels of Cd in all nutrient elements tested with interactions exhibited for iron, manganese, and zinc.